2018
DOI: 10.2337/db18-0667
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Exercise Improves Glucose Metabolism in Adult Offspring

Abstract: Poor paternal diet has emerged as a risk factor for metabolic disease in offspring, and alterations in sperm may be a major mechanism mediating these detrimental effects of diet. Although exercise in the general population is known to improve health, the effects of paternal exercise on sperm and offspring metabolic health are largely unknown. Here, we studied 7-week-old C57BL/6 male mice fed a chow or high-fat diet and housed either in static cages (sedentary) or cages with attached running wheels (exercise tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 43 publications
(64 reference statements)
1
81
1
Order By: Relevance
“…We chose this approach to avoid stress associated with forced exercise protocols in the dams. Recent studies have reported that paternal exercise (>3 weeks) can mitigate the detrimental effects of paternal obesity on offspring glucose tolerance, adiposity, and pancreatic β-cell mass; vascular function was not assessed (McPherson, Lane, Sandeman, Owens, & Fullston, 2017;McPherson, Owens, Fullston, & Lane, 2015;Stanford et al, 2018). In our study, the mating pairs were set up nightly and males were removed immediately after breeding was confirmed (visible by a vaginal plug).…”
Section: Discussionmentioning
confidence: 97%
“…We chose this approach to avoid stress associated with forced exercise protocols in the dams. Recent studies have reported that paternal exercise (>3 weeks) can mitigate the detrimental effects of paternal obesity on offspring glucose tolerance, adiposity, and pancreatic β-cell mass; vascular function was not assessed (McPherson, Lane, Sandeman, Owens, & Fullston, 2017;McPherson, Owens, Fullston, & Lane, 2015;Stanford et al, 2018). In our study, the mating pairs were set up nightly and males were removed immediately after breeding was confirmed (visible by a vaginal plug).…”
Section: Discussionmentioning
confidence: 97%
“…For example, the sperm RNA signature could be used as a clinical marker of offspring metabolic disease susceptibility. In addition, as human sperm RNA profiles are known to be efficiently altered by improved body condition 1,[83][84][85] , the signature could be monitored before a planned pregnancy and clinical guidance (such as improvements to lifestyle) could also be introduced if necessary to reshape the sperm RNA code towards a healthy condition (Fig. 3).…”
Section: Application and Precision Medicinementioning
confidence: 99%
“…The optimal time period(s) to intervene to reduce offspring metabolic risk needs further study (i.e., treatment of pregnant mothers, treatment of affected infants, children, or youth, or a multifaceted approach). Other possible mechanisms should be studied to assess their possible contribution to offspring metabolic outcomes in relation to maternal hyperglycemia, including shared genetics, shared environmentdsimilar diets and exercise patterns as well as chemical exposures (20)dand paternal effects (21,22). Still, with childhood obesity, metabolic disease, and type 2 diabetes being challenging conditions to treat successfully, any interventions that may prevent their emergence should be strongly considered by professional societies and clinicians.…”
mentioning
confidence: 99%